Fimbriae and infectivity in Salmonella typhimurium (Plate XXIX) - Duguid, J. P.; Darekar, M. R.; Wheater, D. W. F. (Journal of Medical Microbiology, 1976)
Summary A genotypically non-fimbriate (Fim−) strain of Salmonella typhimurium and a genotypically fimbriate (Fim+) strain derived from it by spontaneous mutation were compared for pathogenicity in mice. The two strains caused similar numbers of infections and deaths in groups of mice challenged by intraperitoneal inoculation, and nearly similar numbers in groups challenged by inoculation on to the conjunctiva, but the Fim+ strain caused many more infections (plus 26%) and deaths (plus 40%) than the Fim− strain when the inoculation was by mouth. Faecal cultures were made at intervals up to 120 days in the mice surviving after oral or conjunctival challenge and S. typhimurium was isolated more commonly from the animals challenged with the Fim+ strain (906 isolations from 384 animals infected out of 877 challenged) than from those challenged with the Fim− strain (614 isolations from 341 animals infected out of 877 challenged). The greater opportunity for faecal dissemination enjoyed by Fim+ bacteria may account for the preponderance of Fim+ over Fim− strains of S. typhimurium found in mammalian sources.